If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2 = 4x + -11 Reorder the terms: 2 + 2x = 4x + -11 Reorder the terms: 2 + 2x = -11 + 4x Solving 2 + 2x = -11 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + 2x + -4x = -11 + 4x + -4x Combine like terms: 2x + -4x = -2x 2 + -2x = -11 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + -2x = -11 + 0 2 + -2x = -11 Add '-2' to each side of the equation. 2 + -2 + -2x = -11 + -2 Combine like terms: 2 + -2 = 0 0 + -2x = -11 + -2 -2x = -11 + -2 Combine like terms: -11 + -2 = -13 -2x = -13 Divide each side by '-2'. x = 6.5 Simplifying x = 6.5
| 60+c=-10 | | 6(2x+3)-3x=63 | | 7y*4.6= | | 20-5c=50 | | 3/4m=-2/3 | | 5/-9x-2/7x-3 | | -3x+7+2x=37 | | 2/3m=3/4 | | (x^2-4)(x^2-4)=-5 | | 3x+7+2x=37 | | 2x+3+2=-1 | | 2x=103+x | | -2(4x-5)=38 | | 10=25+.5x | | 11=5(n-9) | | 6(9x+18)=60 | | 3/4m=3/7 | | 6(2y+5)=78 | | x/3-19=5 | | -4+5x=87 | | 4p-3=2p+5 | | 5(18+x)+10(4x)+25x=1420 | | 75-5n=100 | | 9x-4x+5=x-5+10 | | f(2)=-3x+9 | | 4(2-4r)=72 | | x-5.1=-7.6 | | -3(2x+1)-(x-3)=-2(x-1)+6x-3(2-x) | | 48-8x=36 | | 1/8(8t-6)=t+6/16 | | 22-(x+9)=6x-8 | | 8/5-7/4y=-5/3 |